A large-scale study on the seroprevalence of Toxoplasma gondii infection in humans in Iran - Kalantari, Reza; Esmaeilifallah, Mahsa; Jafari, Rasool; Mirhendi Esfahani, Hossein; Yousofi Darani, Hossein (Folia parasitologica, 2023)
It is estimated that nearly one-third of the world's human population is infected with Toxoplasma gondii (Nicolle et Manceaux, 1908). Human infection is commonly asymptomatic, multifaceted, and can manifest in severe pathological forms in congenital toxoplasmosis and immunocompromised individuals. This study attempted to recognise the seroprevalence of T. gondii infection in Iranian residents referred to medical laboratories for toxoplasmosis tests throughout the country. This retrospective cross-sectional study was conducted from 2015 to 2019 on individuals referred to diagnostic laboratories in 26 provinces, and these laboratories sent their samples to the referral centres. Accordingly, data associated with serodiagnosis of toxoplasmosis, age, sex, anti-T. gondii IgG, and IgM status in Iranian residents were collected from two referral diagnostic laboratories. All individuals were evaluated using the antibody immunocapture-chemiluminescence assay (CLIA) method with the Immulite®2000s XPi system. In this study, the first large-scale assay of T. gondii infection in Iran, an overall seroprevalence of 30.4% was among 35,047 patients examined. The highest IgM seropositivity rate was in the 10-20 years old patients. In addition, this study showed a very different prevalence of T. gondii across the country, highest in the humid areas, such as the Caspian Sea basin in the North, and the North West with seroprevalence of 48.6%.
Keywords: dospělí; Írán; Prevalence; dítě; chemiluminescence; imunoglobulin G; Toxoplasmosis; antibody; Adult; mladý dospělý; průřezové studie; Adolescent; imunoglobulin M; IgG/IgM; lidé; public health; Toxoplasma; Immunoglobulin G; Risk Factors; retrospektivní studie; séroepidemiologické studie; protilátky protozoální; Iran; Cross-Sectional Studies; Antibodies, Protozoan; Seroepidemiologic Studies; Immunoglobulin M; Young Adult; rizikové faktory; toxoplazmóza; Child; toxoplasmosis; Retrospective Studies; mladiství; Humans